2004
DOI: 10.1093/jjco/hyh006
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Irinotecan in Patients with Metastatic Gastric Cancer Failing Cisplatin-based Chemotherapy

Abstract: This weekly schedule of irinotecan was modestly active against cisplatin-refractory gastric cancer and relatively well-tolerated with appropriate dose modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 22 publications
5
33
0
2
Order By: Relevance
“…In these studies, PFS was reported to range between 2.2 and 4.5 months, whereas OS was reported to vary between 3. 5 and 8 months (Graziano et al, 2000;Giuliani et al, 2003;Chun et al, 2004;Cho et al, 2006;Kodera et al, 2007;Jeong et al, 2008;Sym et al, 2008;Baize et al, 2009;Seo et al, 2009;Kim et al, 2010). In our study, PFS was 3.26 months and OS was 8.76 months.…”
Section: Discussionsupporting
confidence: 61%
“…In these studies, PFS was reported to range between 2.2 and 4.5 months, whereas OS was reported to vary between 3. 5 and 8 months (Graziano et al, 2000;Giuliani et al, 2003;Chun et al, 2004;Cho et al, 2006;Kodera et al, 2007;Jeong et al, 2008;Sym et al, 2008;Baize et al, 2009;Seo et al, 2009;Kim et al, 2010). In our study, PFS was 3.26 months and OS was 8.76 months.…”
Section: Discussionsupporting
confidence: 61%
“…Our study was designed to prove a 1-year survival of 30%, which is somewhat high considering the patients' general condition and proportion of prior exposure to chemotherapy. Nevertheless, this survival rate is a currently acceptable range expected from any new regimen aiming at second-or third-line treatment for gastric cancer (Assersohn et al, 2004;Chun et al, 2004;Wilson et al, 2005;Horinaka et al, 2006).…”
Section: S-1 Monotherapy In Poor Performance Status H-c Jeung Et Almentioning
confidence: 98%
“…A number of agents have previously demonstrated second-line activity in AGC in Phase II trials, with modest benefit; however, no single regimen has shown superior activity [59][60][61][62][63][64]. Several Phase II trials assessing the benefit of targeted second-line therapies have demonstrated ability to achieve disease stabilization (everolimus/RAD001 [65], ramucirumab/IMC-1121B [66], sunitinib [67], cetuximab [68] and lapatinib in HER2-positive disease [69]) and there are a number of ongoing randomized trials assessing the impact of such agents on survival outcomes.…”
Section: Second-line Treatment Of Agcmentioning
confidence: 99%